1984
DOI: 10.1002/art.1780270512
|View full text |Cite
|
Sign up to set email alerts
|

The use of trained patient instructors for teaching and assessing rheumatologic care

Abstract: The training of professionals in rheumatologic care requires review and study. To improve teaching methods, 6 patients with stable rheumatic disease were trained to evaluate and teach medical students by using themselves as models for musculoskeletal examinations. Checklists for scoring performance and content were developed. Criteria established to give evidence of the validity of the checklists and of the reliability of the patient instructors in their scoring were met or exceeded. The patient instructors ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 7 publications
3
37
1
Order By: Relevance
“…Moreover, as previously shown (11,12) and as noted here, arthritis educators are well accepted by physicians-in-training. Finally, the results of this study provide evidence that the significant improvement noted after the arthritis educator intervention persists for at least two weeks.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, as previously shown (11,12) and as noted here, arthritis educators are well accepted by physicians-in-training. Finally, the results of this study provide evidence that the significant improvement noted after the arthritis educator intervention persists for at least two weeks.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, face validity and sampling validity for maneuvers specified in the checklist were previously established by peer judgment, and criterion validity was established by consensus of rheumatologists (11). Similarly, reliability of the checklist as administered by the arthritis educators was previously documented (11) and reconfirmed in the current study. Thus, the evaluation of the students appears to be valid and reasonably objective.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…For example, the use of trained patient instructors who evaluate and teach musculoskeletai examination skills was introduced in the University of Arizona MAC. Preliminary studies of the use of this teaching method indicated that it identified correctable skill deficits in many primary care practitioners (9). Although this technique is now used in many medical schools, its full potential for inclusion in CME programs has not been realized.…”
Section: Education Of Primary Care Practitionersmentioning
confidence: 99%